ISEA2019의 디지털 미디어 전시기획과 인공지능, 데이터 작품 사례 분석 - 김영호(Young-Ho Kim); 오나예(Na-Yea Oh); 박진완(Jin-Wan Park) (디지털콘텐츠학회논문지, 2021)
본 연구는 작품분석논문이자 ISEA(International Symposium on Electronic Art)를 준비하는 과정을 기술한 전시과정기술논문이다. 본문에서는 ISEA의 역할과 CFP(Call for proposal)의 중요성, 전시 경향분석으로 두가지 내용을 다뤘다. 첫 번째로 ISEA의 역할과 CFP의 중요성을 확인하고 2019 ISEA 심포지엄을 전체적으로 아우를 수 있는 주제를 작성했다. 두 번째로 현대의 예술가들이 데이터와 인공지능을 해석하는 경향을 살펴보고, 작품에서 어떻게 표현했는지를 관찰했다. ISEA 2019에서는 작가들이 정의하는 인공지능에 관한 다양한 관점이 제시되었다. 이를 통해 작품 경향에서는 데이터를 바라보는 작가의 해석 범위가 확대된 것을 확인할 수 있었다. 또한 본 논문을 통해 향후에 데이터 기반 예술의 전시 기획 때 범용적인 방법론으로 기여할 수 있을 것이다. This research is an artwork analysis paper and an exhibition process explanation paper that describes the process of preparing ISEA(International Symposium on Electronic Art). This paper suggests two main topics: the role of ISEA and the importance of CFP(Call for proposal), and the analysis of exhibition trends. First, this study finds out the role of ISEA and the importance of CFP and deals with a topic that could encompass overall 2019 ISEA Symposium. Secondly, this study researches the tendency of modern artists interpreting the data and artificial intelligence and observes how they express them in their works. In ISEA 2019, various perspectives on artificial intelligence, that are defined by artists, were presented. Through that, it was confirmed that the scope of interpretation of the artist looking at the data are expanded in the tendency of the work. Moreover, this paper contributes to the universal methodology of planning future exhibitions of data-based art. KCI Citation Count: 1